Pengaruh Pemanfaatan Teori Super Dalam Layanan Penempatan Dan Penyaluranterhadap Pengambilan Keputusan Karir Siswa - Zaleha Zaleha; Muhammad Subhan (Fakultas Tarbiyah dan Keguruan, 2020)
Career decision-making was an important step for high school students. In career decision-making should also be adapted to the capabilities of the students themselves. This research aimed at knowing the influence of utilization of Super theory on Placement and Distribution service toward student career decision-making at Vocational High School of Multi Mekanik Masmur Pekanbaru students. Quantitative method was used in this research with simple linear regression data analysis technique. The eleventh-grade students were the population of this research. Simple random sampling technique was used in this research. Questionnaire and documentation were the techniques of collecting the data. The requirements to use simple linear regression analysis were implemented. The results of this study there is the influence of variable X on variable Y can be seen by looking at the value of R Squere which is 0.157 which means that the variable X to the variable Y is 15.7%. In other words, the use of the Super theory in placement and channeling services has a 15.7% effect on career decision making for students of the Multi Mechanic Vocational High School of the Masmur Pekanbaru, and 84.3% was influenced by other factors. It was recommended to the next researchers to study about other variables, except the variable studied.